Effectiveness of Molase and Fruit Waste Liquid Organic Fertilizer in Baglog Media on the Growth and Production of White Oyster Mushroom (Pleurotus ostreatus) - Pinkya Nissa Penida; Kabul Warsito; Muhammad Hafiz (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
Fungal growth is influenced by various kinds of additional nutrients provided, including the addition of molasses and liquid organic fertilizer from fruit waste. The purpose of this study was to examine the effect and interaction of adding molasses and liquid organic fertilizer on baglog media on the growth and production of white oyster mushroom (Pleurotus ostreatus). The research was conducted from May-July 2022 at the Center for Breeding and Development of Oyster Mushroom Cultivation on Sunggal District, Deli Serdang Regency. The research method used was a 2-factor factorial Completely Randomized Design (CRD), 16 treatment combinations and 2 replications so that there were 32 baglogs. The first factor consisted of 4 levels of treatment, namely M0: no treatment (control), M1: 7.5 ml/baglog, M2: 15 ml/baglog and M3: 22.5 ml/baglog. The second factor consisted of 4 levels of treatment, namely P0: no treatment (control), P1: 7.5 ml/baglog, P2: 15 ml/baglog and P3: 22.5 ml/baglog. Parameters observed were mycelium growth rate (cm), stalk height (cm), hood diameter (cm), hood thickness (mm), number of branches/clumps, and wet weight (g). In the mycelium growth rate parameter, the highest data was found in the P0 treatment of 20.62 cm. In the stalk height parameter, the highest data was found in the M0 treatment of 7.17 cm. In the hood diameter parameter, the highest data was found in the M2 treatment of 10.55 cm. In the hood thickness parameter, the highest data was found in the M2 treatment of 5.11 mm. In the parameter of the number of branches, the highest data is found in the P3 treatment of 9.63. In the wet weight parameter, the highest data in the P3 treatment was 126.38 g.